Computational thermodynamics and microstructure simulations to understand the role of grain boundary phase in Nd-Fe-B hard magnets. Issue 1 (31st December 2021) - Koyama, Toshiyuki; Tsukada, Yuhki; Abe, Taichi
ABSTRACT: To control the coercivity of Nd hard magnets efficiently, the thermal stability of constituent phases and the microstructure changes observed in hard magnets during thermal processes should be understood. Recently, the CALPHAD method and phase-field method have been recognized as promising approaches to realize phase stability and microstructure developments in engineering materials. Thus, we applied these methods to understand the thermodynamic feature of the grain boundary phase and the microstructural developments in Nd-Fe-B hard magnets. The results are as follows. (1) The liquid phase is a promising phase for covering the Nd2 Fe14 B grains uniformly. (2) The metastable phase diagram of the Fe-Nd-B ternary system suggests that the tie line end of the liquid phase changes drastically depending on the average composition of Nd. (3) The Nd concentration in the grain boundary phase can reach 100 at% if the volume fraction of the grain boundary phase is constrained. (4) The effect of Cu addition to the Nd-Fe-B system on the microstructural morphology is reasonably modeled based on the phase-field method. (5) The morphology of the liquid phase can be controlled using phase separation in the liquid phase and the grain size of the Nd2 Fe14 B phase. Graphical Abstract: uf0001